Education On Processing And Handling Of Green Shells To Fisherman In Ujung Pangkah District, Gresik Regency - Handarini , Kejora; Rachmiati , Retnani; Djauhari , Arlin Besari; Madyowati, Sri Oetami; Kusyairi, Achmad; Sumaryam, Sumaryam; Noor, M Tajuddin; Yuniarti, Maulidia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2022)
Banyu Urip Mangrove Center (BMC) is one of the Mangrove tourist areas, which also has green mussel cultivation around it. Green mussels in this area tend not to be processed into preserved food products, but are only traded fresh. The price of fresh green mussels is very cheap, therefore it is necessary to increase knowledge regarding the diversification of processed green mussels to increase the added value of green mussels and the knowledge of mothers in the BMC area, Ujung Pangkah District, Gresik Regency. To solve this problem, the role of higher education is needed, including carrying out community service through outreach to mothers in the area. The purpose of this activity is to educate mothers about processed diversification and handling of green mussels. The method of implementing this activity consists of 3 stages, namely: preparation, implementation of counseling, and evaluation. The result of this activity was an increase in the knowledge of mothers about the variety of diversification of processed green mussels including: Green Mussel Shell Flour, Green Mussel Crackers, Condiment Pasta (Such as Oyster Sauce), Green Scallop Meatballs, Green Scallop Nuggets, and Chitosan. The mothers looked very enthusiastic about participating in this activity as shown by the very interactive questions and answers and discussions, as did the participants who remained in place until the end of the event.